Islamic Ruling of Consuming Meat-Birds that Go through the Contemporary Scalding and Evisceration Process - Mohammed Mouaz bin Maulana Abed Ali Hafeji; Mohammed Farid Ali al-Fijawi (Penerbit Hellow Pustaka, 2024)
Islam requires the consumption of meat that has been sourced from an animal that has been slaughtered, processed, and delivered according to the Islamic requirements. The lawful status of meat is not tied to the slaughtering only. The processes of plucking feathers, removing entrails, etc., all have to be taken into consideration before the meat can be deemed lawful (halāl) and wholesome (tayyab). The nominal process in Islam to avoid impurity and contamination of the meat is to remove the entrails before immersing the chicken in hot water to soften the feathers for plucking. However, the current industrial practice switches this process. The mechanical plants are designed to immerse the chicken in hot water and pluck the feathers before gutting the chicken. This has given rise to inquiries and doubts to the Muslim consumers whether the meat of such birds are lawful or not. In order to provide an Islamic response to this issue, this paper is looking into, first the scientific and industrial perspective of the scalding and evisceration processes. Second, the paper is evaluating the scientific-industrial practice in the light of Islamic jurisprudence (Fiqh).